2004
DOI: 10.1002/hep.20013
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected artifacts raise new caution in stem cell culture research

Abstract: With this letter, we wish to raise caution about interpretations of results owing to artifacts that may occur when cell lines are derived by culturing on cell-derived feeder layers. We recently reported the apparent derivation of rat liver progenitor cell lines by co-culture of liver cells enriched in periportal oval cells after allyl alcohol injury with ␥-irradiated mouse STO (SIM [Sandoz inbred Swiss mouse]) fibroblast feeder layers. 1 These reported lines are now undergoing intensive reinvestigation in our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2005
2005

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…However, subsequent work identified that these markers were associated with cells likely derived from the mouse embryonic feeder layer rather than the rat (Zhang et al . 2003; Leffert & Sell 2004).…”
Section: Adult Liver As a Source Of Progenitor Cellsmentioning
confidence: 99%
“…However, subsequent work identified that these markers were associated with cells likely derived from the mouse embryonic feeder layer rather than the rat (Zhang et al . 2003; Leffert & Sell 2004).…”
Section: Adult Liver As a Source Of Progenitor Cellsmentioning
confidence: 99%